2022
DOI: 10.3389/fgene.2022.931659
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis and Evolutionary Perspective of the Cytokinin Dehydrogenase Gene Family in Wheat (Triticum aestivum L.)

Abstract: Cytokinin dehydrogenase (CKX; EC.1.5.99.12) regulates the level of cytokinin (CK) in plants and is involved in CK regulatory activities. In different plants, a small gene family encodes CKX proteins with varied numbers of members. These genes are expanded in the genome mainly due to segmental duplication events. Despite their biological importance, CKX genes in Triticum aestivum have yet to be studied in depth. A total of 11 CKX subfamilies were identified with similar gene structures, motifs, domains, cis-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…The abundance of elements in the promoter region of GhCKX genes suggests the functional diversity of these genes in cotton. Furthermore, GhCKX genes harbor cis -elements in their promoter regions associated with a stress response (low-temperature and drought response) and hormone response elements (salicylic acid response, auxin response, abscisic acid response, gibberellin response, and methyl jasmonate (MeJA) response elements) were consistent with prior studies in soybean ( Du et al, 2023 ) and wheat ( Jain et al, 2022 ). The occurrence of different elements in the GhCKX genes’ promoter region indicate their functional diversity in cotton…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The abundance of elements in the promoter region of GhCKX genes suggests the functional diversity of these genes in cotton. Furthermore, GhCKX genes harbor cis -elements in their promoter regions associated with a stress response (low-temperature and drought response) and hormone response elements (salicylic acid response, auxin response, abscisic acid response, gibberellin response, and methyl jasmonate (MeJA) response elements) were consistent with prior studies in soybean ( Du et al, 2023 ) and wheat ( Jain et al, 2022 ). The occurrence of different elements in the GhCKX genes’ promoter region indicate their functional diversity in cotton…”
Section: Discussionsupporting
confidence: 86%
“…The analysis of GhCKX gene structures show that they have multiple introns and exons, and the CKX members of a subgroup, that are closely related, have similar gene structure and domain composition, which may indicate comparable developmental functions in the plant. Previous studies have found that the number of exons/introns of CKX gene family members ranges from 1 to 4 in wheat ( Jain et al, 2022 ), and from 1 to 10 in soybean ( Du et al, 2023 ). In this study, the number of exons/introns in G. hirsutum ranged from 8 to 18, which is consistent with the number of exons/introns in Phaseolus vulgaris ( Zhang et al, 2023 ), suggesting that the exons/introns of CKX genes were deleted or inserted during the evolution of G. hirsutum .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CKX7 was expressed at low levels in leaf, inflorescence, and spike tissues. CKX4 and CKX5 were expressed at higher levels in leaf tissues [13]. CKX3 and CKX11 were expressed at different levels in all the tissues studied, while CKX10 was expressed at lower levels in all tissues except leaves [13].…”
Section: Introductionmentioning
confidence: 88%
“…CKX4 and CKX5 were expressed at higher levels in leaf tissues [13]. CKX3 and CKX11 were expressed at different levels in all the tissues studied, while CKX10 was expressed at lower levels in all tissues except leaves [13]. BjuCKX11 and BjuCKX13 were significantly up-regulated in the S2 phase, which had the highest expression levels among the four periods, while the highest expression levels of BjuCKX12 and BjuCKX14 occurred in the S4 phase [14].…”
Section: Introductionmentioning
confidence: 90%